THE BEAUTY OF PURITY, TRANSFORMATION AND RENEWAL - Corner, Creative (Journal of Pakistan Psychiatric Society, 2024)
Traditionally, rare and striking creatures are revered as powerful emblems of transformation and personal growth. One such symbol is a bird that embodies purity, renewal, and spiritual awakening. With its extraordinary appearance, this bird represents not only beauty but also resilience—the ability to overcome challenges and emerge stronger. It serves as a reminder that healing and growth are possible despite adversity. This symbolism is most powerfully portrayed by the white peacock, whose rare and serene presence highlights the potential for profound transformation, inner peace, and the beauty found in renewal. As a metaphor of strength, this magnificent being encourages us to embrace our uniqueness, find beauty in our struggles, and pursue balance in our mental and emotional well-being. The white peacock’s rare presence provides us a compelling inspiration, that like this majestic bird, we too can rise above our challenges and emerge into a new chapter of growth and self-discovery.